Creation of prosocial play experiences inspired by Noddings’s ideas of centers of care - Krystyna Nowak-Fabrykowski; Ranay Gursky; Stephanie Keck-Warren (Problemy Wczesnej Edukacji)
This paper describes the implementation of Noddings’s ideas of creating centers as a platform for developing in children caring, prosocial behavior. Different centers such as a veterinary center, grocery store, house, baby center, woodworking center, hairdressing, block center, and composting and recycling activities based on play, provide opportunities for stimulating the social development of children and create a caring community of learners based on sharing, helping each other, working as a team and caring for others’ wellbeing.